Environmental engineering : environmental health and safety for municipal infrastructure, land use and planning, and industry - Nemerow, Nelson L.; Agardy, Franklin J.; Sullivan, Patrick; Salvato, Joseph A. (Hoboken : Wiley / John Wiley & Sons, 2009)
First published in 1958, Salvato's Environmental Engineering has long been the definitive reference for generations of sanitation and environmental engineers. Approaching its 50th year of continual publication in a rapidly changing field, the Sixth Edition has been fully reworked and reorganized into three separate, succinct volumes to adapt to amore complex and scientifically demanding field with dozens of specializations.Updated and reviewed by leading experts in the field, this revised edition offers new coverage of industrial solid wastes utilization and disposal, the use of surveying in environmental engineering and land use planning, and environmental assessment. Stressing the practicality and appropriateness of treatment, the Sixth Edition provides realistic solutions for the practicing public health official or environmental engineer.This volume, Environmental Health and Safety for Municipal Infrastructure, Land Use and Planning, and Industry, Sixth Edition, covers:Municipal and industrial waste and pollution including landfills and facility, office and residential sanitation, and air qualityThe environmental health of residential and institutional spaces such as homes and offices, including indoor air quality, sanitation, and the impact of substandard construction techniquesLand use planning and forensics techniques for investigating repurposed industrial and agricultural landAir pollution and noise controlSurveying and mapping for environmental engineering
Obsahuje údaje o editoroch
Obsahuje terminologické slovníky
Obsahuje bibliografie a register
Keywords: environmentálne inžinierstvo; Environmental engineering; urbanizmus; Urbanism; ochrana životného prostredia; Environmental protection; priemyselný odpad; Industrial waste; kolektívne monografie; Collective monographs